Earth protection system for AC substation - Loo, Kok Hoong (2016)
The earth protection system, also known as grounding system, is to protect the equipment in the substation by providing low impedance path for fault current flow to the earth. In addition, this system plays a significant role in safety assurance of the personnel working within or nearby of the stations. In order to meet the power system performance and electrical safety, the earth resistance needs to be low enough for the required level of fault current to flow. Also, dangerous potential gradient of fault current should not arise to any metal or conducting equipment from the ground. As Singapore has underground power transmission and distribution system, earth protection is vitally important. The objective of this dissertation is to analyze the schemes of earth protection system with its different parameters, and associated effects in the AC electrical substations in Singapore geographical areas. In order to analyze the scheme of earth protection system, calculations on earth conductor sizing, scheme resistance, the criteria and permissible imposed touch and step voltage levels have been conducted. Local authorities’ standard requirements and guidelines of typical AC substations in Singapore are also presented. Equations and Matlab simulations on case study examples have been generated to determine the design scheme achieve the safety level.